Exercise capacity in a 78 year old patient with McArdle's disease: it is never too late to start exercising. Issue 8 (21st July 2006) - Perez, M; Martin, M A; Rubio, J C; Maté-Muñoz, J L; Gómez-Gallego, F; Foster, C; Andreu, A L; Arenas, J; Lucia, A
Abstract : The case is reported of a 78 year old man with McArdle's disease and a history of treated coronary heart disease. Despite the pre-exercise administration of sucrose allowing the patient to exercise with normal physiological responses, and without typical McArdle's symptoms or biochemical evidence of muscle damage, his exercise capacity was very low (V̇o 2 peak = 10.7 ml/min/kg), probably attributable to his lifetime of sedentary living. The data suggest that, with pre-exercise sucrose administration, such patients may be candidates for systematic reconditioning, which may improve functional capacity and quality of life.